Stressed-Out Oral Immunity: A Gateway From Socioeconomic Adversity to Periodontal Disease. Issue 2 (February 2020) - Gomaa, Noha; Glogauer, Michael; Nicolau, Belinda; Tenenbaum, Howard; Siddiqi, Arjumand; Fine, Noah; Quiñonez, Carlos
ABSTRACT: Objective: It has been suggested that adverse socioeconomic conditions "get under the skin" by eliciting a stress response that can trigger periodontal inflammation. We aimed to a) estimate the extent to which socioeconomic position (SEP) is associated with periodontal disease (PD) and proinflammatory oral immunity, and b) determine the contribution of psychosocial stress and stress hormones to these relationships. Methods: In this cross-sectional study ( n = 102), participants (20–59 years old) completed financial and perceived stress questionnaires and underwent full-mouth periodontal examinations. SEP was characterized by annual household income and educational attainment. Cortisol, a biological correlate of chronic stress, was assessed in hair samples. Oral immunity was characterized by assessing oral inflammatory load and proinflammatory oral neutrophil function. Blockwise Poisson and logistic regression models were applied. Results: Compared with lower SEP, individuals in the middle- and higher-income categories had a significantly lower probability of PD (incidence rate ratio [IRR] = 0.5 [confidence interval CI = 0.3–0.7] and IRR = 0.4 [95% CI = 0.2–0.7]) and oral inflammatory load (IRR = 0.6 [95% CI = 0.3–0.8] and IRR = 0.5 [95% CI = 0.3–0.7]) and were less likely to have a proinflammatory oral immune function (odds ratio [OR] = 0.1 [95% CI = 0.0–0.7] and OR = 0.1 [95% CI = 0.0–0.9]). PD and oral immune parameters were significantly associated with financial stress and cortisol. Adjusting for financial stress and cortisol partially attenuated the socioeconomic differences in PD to IRR = 0.7 (95% CI = 0.5–0.8) and IRR = 0.6 (95% CI = 0.5–0.7) for the middle- and higher-income categories, respectively. Similar results were observed for proinflammatory immunity (OR = 0.2 [95% CI = 0.0–1.8] and OR = 0.3 [95% CI = 0.0–2.3]). Conclusion: These findings suggest that psychosocial stress may contribute to a proinflammatory immunity that is implicated in PD pathobiology and provide insight into social-to-biological processes in oral health. Abstract : Supplemental digital content is available in the text.